Neutrino Tomography with Artificial Neutrino Beams: A Novel Approach to Probing Earth's Internal Structure and Density Profile - Haas, Andy; Xiang, Gengbo (International Core Journal of Engineering, 2025)
Understanding Earth's internal structure is critical for geophysical sciences, but traditional seismic tomography faces limitations such as the inability of S-waves to penetrate the liquid outer core and the difficulty in distinguishing minerals with similar seismic velocities. This study proposes a novel approach using neutrino tomography with artificial neutrino beams to address these challenges. Neutrinos, due to their weak interaction properties, can traverse the entire Earth, making them ideal probes for deep interior exploration. The methodology involves constructing a six-layer spherical Earth model (Continental Crust, Upper Mantle, Transition Zone, Lower Mantle, Outer Core, and Inner Core) based on the Preliminary Reference Earth Model (PREM). By simulating neutrino beams with fixed energy (10 GeV) propagating along six distinct trajectories through these layers, the absorption and survival probabilities of neutrinos are calculated using the Bouguer-Beer-Lambert Law and neutrino-nucleon interaction theory. A system of linear equations is derived to invert the Earth's density profile from the simulated survival data, validated through Monte Carlo simulations (1000 iterations with 10,000 neutrinos per path). Results show strong consistency between inverted densities and PREM, with a maximum relative error of 0.67% (Transition Zone) and a root-mean-square error (RMSE) of ~0.023 g/cm³. Notably, the inner core exhibits the smallest relative error (0.15%), highlighting neutrino tomography's unique advantage in penetrating high-density regions inaccessible to seismic S-waves. This study demonstrates the feasibility of neutrino tomography as a complementary tool to seismic methods, offering new insights into Earth's composition and dynamics with implications for geophysics, planetary science, and resource exploration.